Utilization of biodegradable carrier-based nano herbicide formulations for sustainable weed management in agriculture - Jayasoorya, Rajasekaran; Kumar, Pradeesh (Frontiers in Agronomy, 2024)
Recently, the injudicious use of herbicides in agriculture is causing numerous hazards that affect the environment and living organisms. To achieve the SDG 2030 agenda goal 12- “Ensure sustainable consumption and production patterns,” there is an urgent need to shift towards using toxic-free agricultural inputs. Various techniques are widely adopted to control weed growth and development, but farmers mostly rely on herbicide application. Nanotechnology-enabled herbicide formulations are more sustainable and efficient in weed control than traditional sources. The nanoherbicides enable lesser application frequency and minimum quantity requirement, thereby preventing herbicide accumulation in soil and water bodies. Mainly nano-mediated biodegradable carrier-based herbicides possess properties of prolonged release, targeted inhibition, reduced mobility in soil, better adhesion to the plant surface, and retards rapid degradation of active ingredients (AIs), which increase herbicide use efficiency against weeds. Biodegradable carrier materials are cost-effective and readily available from living/non-living organisms and mineral sources, which can be an alternate source for metal/metal-oxide carrier materials. Materials like chitosan, plant derivatives, clay particles, and synthetic polymers are notable carrier materials reported for encapsulating or loading herbicide molecules. Applying nano-mediated herbicides is an innovative methodology for controlling weeds while considering environmental safety. This review focused mainly on recent advances in biodegradable carrier-based herbicide application in agriculture to mitigate the crisis in sustainable weed management. The ultimate objective of this manuscript is to serve as a source of reference material for exploring the nano-based herbicide formulations, their mobility, fate, and future perspectives.